Strengthening Fiqhul Bi'ah Character in Islamic Religious Education at Public Elementary Schools - Lalu Habiburrahman Habib (IQRO: Journal of Islamic Education, 2026)
ABSTRACT This study aims to examine and describe the efforts to strengthen fiqhul bi'ah (Islamic environmental jurisprudence) character in Islamic Religious Education (IRE) learning among 5th grade students at SDN 2 Sukadana Kecamatan Bayan Kabupaten Lombok Utara. The increasingly alarming ecological crisis demands a serious response from the world of education, including education based on Islamic values. Fiqhul bi'ah, as a branch of Islamic jurisprudence governing the relationship between humans and the environment, is highly relevant to be integrated into IRE learning at the elementary school level. The research employed a qualitative descriptive approach with data collected through observation, in-depth interviews, and document analysis. The results indicate that fiqhul bi'ah character strengthening among 5th graders at SDN 2 Sukadana Kecamatan Bayan Kabupaten Lombok Utara can be implemented through three main strategies: (1) integrating fiqhul bi'ah concepts into IRE materials based on the Merdeka Curriculum; (2) habituation of Islamic ecological behavior in daily school life; and (3) teacher exemplary conduct and parental involvement in building ecological piety. The strengthening of fiqhul bi'ah character has been proven effective in raising students' environmental awareness grounded in the values of tawhid, khalifatullah, and maqashid al-shari'ah. Keywords: fiqhul bi'ah; ecological character; Islamic religious education; maqashid al-shari'ah